Studi Tata Letak Fasilitas di Pelabuhan Perikanan Nusantara Brondong Kabupaten Lamongan Propinsi Jawa Timur - Jonny Zain (Universitas Riau, 2009)
This study was conducted on August 2008 in Brondong Fishing Port, Lamongan District, East Java Province and survey method was used. The aims of this study was toobserve spatial planning facilities based on fishing and fishermen supporting activities andtried to obtain some solutions on issues were found. The result show, spatial planningfacilities on Brondong fishing port are relatively appropriate where each facility locate onit’s space those improve efficiency and affectivity facilities. Some issues were found;Brondong fishing port had large fisheries activities since it has large number of fishingvessel landed and others activities then its capacity.